Public participation as a tool for the realisation of socio-economic rights: the pitfalls of state organised spaces of participation - Phama, Wandisa (Department of Public Law, 2018)
This paper seeks to investigate the legal structures and sources which provide for the obligations of the state to facilitate public participation in the realisation of socio-economic rights. The paper further explores the different interpretations of the notion of public participation in an attempt to critique and interrogate which kind of public participation actually allows for communities to meaningfully participate in the processes of the state to realise socio-economic rights. The paper will argue that the effectiveness of the state in facilitating public participation in its affairs depends on the notion of public participation adopted in a particular state. It will further argue that the effectiveness of such participation by communities is dependent on the understanding that meaningful spaces for participation occur through power contestations. Participation may mean very little for the realisation of socio-economic rights if the power of the state over citizens is not challenged and contested in spaces of participation. The paper will argue that for public participation to be meaningful in the realisation of socio-economic rights, it needs to occur in spaces in which the state will not have too much power over citizens to an extent that their participation is just for display. It will further argue that it is how people are perceived by the state and how they perceive themselves as citizens which determines their ability to challenge the state's power in spaces of participation. When communities are treated as citizens because of the rights they have, public participation processes to discuss the provision of basic services are then facilitated with the understanding of how communities can partner with the state with influence and power that is required to take decisions to realise their rights. It is submitted that part of the frustration with the exclusion in spaces where socio-economic rights enforcement decisions are taken is created by how South Africans as citizens are not always treated as rights bearers who can challenge the state. The exclusion of communities from planning for service delivery by the state has become internalised by some communities as part of the rules of the game of governance. Such internalised exclusion is a major contributing factor in the increased frustration with slow service delivery and a government that is unaccountable to the people. The paper will argue that for public participation to be an effective tool in the realisation of socio-economic rights taking into account the theories of power, space and citizenship there is a need for public education on how communities can demand a responsive behaviour from the state beyond protests. There is further need for state officials for example to attend workshops on their obligations to facilitate public participation in planning for the realisation of socio-economic rights when they take office. The paper will further argue that, in order for public participation to be effective in contributing to the realisation of socio-economic rights, Chapter 9 institutions also need to play a more active and visible role in communities and assist to hold the state accountable to facilitate public participation as that is one of the most important factors in the realisation socio-economic rights. The paper will argue that, although public participation is but one tool in the arsenal of tools to facilitate the realisation of socio-economic rights, it is important for many reasons. It is important for the manner in which it creates a space for decisions to be taken in an inclusive manner. The involvement of communities in the decision making processes of the state also legitimises the decisions so taken. Meaningful and inclusive public participation allows for a situation in which various options are put on the table in dialogues between the state and communities so that when a particular outcome is reached it could be what is best for those communities as other perspectives are heard and discussed.